Liquid-liquid phase separation-driven molecular subtyping and prognostic modeling in colorectal cancer - Guan, Hui; Tian, Chengzi; Lin, Jiawen; Zhang, Lihuan; Shi, Run; Wang, Wenjing; Li, Shuping; Sui, Yuan; Lu, Yanwen; Cui, Tianjiao; Chen, Duo (Frontiers in Immunology, 2026)
BackgroundLiquid–liquid phase separation (LLPS) orchestrates the spatiotemporal organization of biomolecular condensates and regulates numerous biological processes. However, the extent to which dysregulated LLPS facilitates the progression of colorectal cancer (CRC) has not been elucidated. Elucidating how LLPS influences CRC possibly offers valuable insights into diagnosis and therapeutic intervention.MethodsDifferentially expressed genes (DEGs) were identified from 566 CRC samples and 19 normal controls in the GSE39582 dataset. LLPS-linked genes were collected from the DrLLPS database. Prognostically significant genes were identified via univariate Cox regression, least absolute shrinkage and selection operator regression, and stepwise akaike information criterion algorithm. The risk score was derived utilizing the LLPS-linked gene signature. Patient characteristics were evaluated concerning the computed risk scores. The biological and clinical distinctions across high-risk and low-risk cohorts were further investigated, leveraging the COAD, READ, and GSE17536 validation cohorts. The expression and spatial distribution of the five prognostic genes were examined via the GSE166555 dataset and spatial transcriptomics analysis. The hydroxyacyl-coenzyme A dehydrogenase (HADH) expression-related enrichment pathways were further analysed via weighted gene coexpression network analysis combined with Metascape. The expression and biological functions of HADH were verified in vitro.ResultsA total of 430 LLPS-related DEGs were identified, from which five prognostic genes were selected to construct the LLPS-associated risk signature. Marked differences in gene expression profiles, overall prognosis, clinicopathological attributes, somatic mutations, signaling pathway activity, tumor microenvironment composition, and drug sensitivity were noted across the high-risk and low-risk populations. Furthermore, the expression of the five prognostic genes and biological functions of HADH were validated through in vitro experiments.ConclusionsAn LLPS-related prognostic model was created, enabling the stratification of the CRC population according to risk and informing individualized therapeutic strategies.